The impact of the CAP Health Check on the price relations of the EU food supply chain: a dynamic panel data cointegration analysis. (22nd April 2021) - Rezitis, Anthony N.; Rokopanos, Andreas
The CAP Health Check at the end of 2008 attested to the liberalisation initiated in the 2003 CAP Reform concerning the policy measures intended to protect farmers across Europe. It was agreed that several restrictions, including the remaining coupled payments, the set-aside requirements and the milk quotas, would be removed. This study investigates the price relations along the EU food supply chain based on a panel cointegration and error correction vector autoregressive approach. Our panel data comprise monthly observations from January 2005 to September 2012 in 19 European countries. The sample is split into two sub-periods, January 2005 to December 2008 and January 2009 to September 2012, to examine how the CAP Health Check has affected price relations. The empirical results indicate that the decreased support in the agricultural sector after the CAP Health Check has rendered agricultural prices more respondent to market signals, suggesting a more liberalised market.